Descriptive sensory analysis of marinated and non-marinated wooden breast fillet portions1. (11th July 2018) - Maxwell, A D; Bowker, B C; Zhuang, H; Chatterjee, D; Adhikari, K
Abstract: The wooden breast (WB) myopathy influences muscle composition and texture characteristics in broiler breast meat. It is unknown if marination reduces the negative influence of WB on meat sensory quality or if WB effects are uniform throughout the Pectoralis major . The objective of this study was to determine the effects of marination on the sensory attributes and instrumental shear force measurements of the ventral (skin-side) and dorsal (bone-side) portions of normal and severe WB meat. Sixty butterfly fillets (30 normal and 30 severe WB) were selected from the deboning line of a commercial processing plant. Individual fillets were portioned into ventral and dorsal halves. Portions from one side of each butterfly were used as non-marinated controls, and portions from the other side were vacuum-tumble marinated (16 rpm, −0.6 atm, 4°C, 20 min) with 20% (wt/wt) marinade to meat ratio. Marinade was formulated to target a concentration of 0.75% (w/v) salt and 0.45% (w/v) sodium tripolyphosphate in the final product. Descriptive sensory analysis (9 trained panelists) was conducted to evaluate visual, texture, and flavor attributes (0–15 point scale) of breast portions along with Warner-Bratzler shear force. Significant interaction effects between WB and marination were not observed for the sensory attributes. Greater springiness, cohesiveness, hardness, fibrousness, and chewiness scores were observed in WB samples ( P < 0.001). Marination decreased cohesiveness, hardness, and chewiness ( P < 0.05) and increased juiciness ( P = 0.002). The effects of WB on sensory texture attributes were more apparent in the ventral portions of the breast fillets. Flavor attributes (salty and brothy) increased ( P < 0.001) with marination. In non-marinated samples, shear force was similar between normal and WB samples. In marinated samples, however, shear force was greater ( P < 0.001) in WB samples. Data suggest that the WB effect on meat sensory quality is not uniform throughout the Pectoralis major and that WB-related differences in cooked meat sensory texture attributes are lessened but not eliminated by vacuum-tumbling marination.